Grlom u jagode (Epizoda 6) - Spoljni izgled . With a Throat into Strawberries (Episode 6) - Outward Appearance - Karanović, Srđan (RTV Beograd, 1975)
The sixth episode focuses on the dress habits of Bane and his generation. The core of the story follows Bane’s attempt to change his outward appearance and buy his own suit in another effort to become more serious. In the process Bane falls in love with the daughter of his tailor and, greatly encouraged by his adventurous grandmother, almost leaves with her for Paris. Finally he changes his mind and stays in Belgrade, continuing his dull student life.